Analysis of Factors Associated with the Performance of HIV/AIDS Program Managers at the East Kutai District Health Service - Rikka Oktora; Ratno Adrianto; Ratih Wirapuspita Wisnuwardani; Ratna Wati (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
It turns out that the East Kutai District Health Service has not been able to increase the SPM HIV/AIDS performance achievement to 100% in East Kutai District. This is proven by the SPM achievement still being at 98% in 2022 and 92% in 2023. Many factors are related to the performance of program managers, including the availability of infrastructure, motivation, opportunities and health services. This research aims to determine factors related to the performance of HIV/AIDS program managers at the East Kutai District Health Service. This research method is quantitative with a total sample of 50 people, data analysis uses statistical correlation analysis using the che squere test. The research results show that the relationship between infrastructure and the performance of HIV/AIDS program managers with a sig value of 0.000 means sig < α (0.05). The relationship between motivation and the performance of HIV/AIDS program managers with a sig value of 0.010 means sig < α (0.05). The relationship between opportunities and the performance of HIV/AIDS program managers with a sig value of 0.000 means sig < α (0.05), and the relationship between health services and the performance of HIV/AIDS program managers with a sig value of 0.001 means sig < α (0.05). This research concludes that there is a significant relationship between the availability of infrastructure, motivation, opportunities and health services and the performance of HIV/AIDS program managers at the East Kutai District Health Service. This requires efforts to increase the speed and accuracy of the distribution of infrastructure, provide space for team member creativity, provide incentives and rewards to employees, open up opportunities for team member career advancement and bring services closer to the community with easy and affordable services, especially for HIV/AIDS patients. Keywords: Performance, HIV/AIDS Program